2022
DOI: 10.1002/art.42248
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Immune Cell Profiling in Patients With Early Systemic Lupus Erythematosus

Abstract: Objectives To investigate the immune cell profiles of patients with systemic lupus erythematosus (SLE), and to identify longitudinal changes in those profiles over time. Methods We employed mass cytometry with 3 different panels of 38–39 markers (an immunophenotyping panel, a T cell/monocyte panel, and a B cell panel) in cryopreserved peripheral blood mononuclear cells (PBMCs) from 9 patients with early SLE, 15 patients with established SLE, and 14 controls without autoimmune disease. We used machine learning–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
5
18
0
Order By: Relevance
“…The analysis revealed that cT FH cells were expanded in the early phase of lupus and decreased longitudinally, while a recently described cell type, namely, peripheral T helper cells (T PH ), remained elevated during the first year post-enrollment. Their hypothesis was that T FH -B cell interactions in lymphoid tissues may be important at the onset of the disease, which may then be changed to T PH -B cell interplay at the site of inflammation in time [ 45 ]. Interestingly, when they measured the correlation between serum chemokine levels and immune cells, CCL20 was strongly correlated with expanded cT FH cells.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that cT FH cells were expanded in the early phase of lupus and decreased longitudinally, while a recently described cell type, namely, peripheral T helper cells (T PH ), remained elevated during the first year post-enrollment. Their hypothesis was that T FH -B cell interactions in lymphoid tissues may be important at the onset of the disease, which may then be changed to T PH -B cell interplay at the site of inflammation in time [ 45 ]. Interestingly, when they measured the correlation between serum chemokine levels and immune cells, CCL20 was strongly correlated with expanded cT FH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian inflammation and damage induced by part of autoantibodies can also lead to decreased ovarian reserve (DOR) or premature ovarian failure (POF) ( 36 ). Meanwhile, there was much evidence of immune imbalance in patients with SLE, such as regulatory T cell dysfunction ( 37 ) and abnormal production of multiple cytokines ( 38 ) which contributed to decreased ovarian reserve. In addition, a study evaluated the lymphocyte subpopulation in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD8 + T cells in SLE is gaining interest. Their cell numbers are increased in early lupus and are present in the interstitium of kidneys from patients with nephritis 201 202. The contribution of IFN-I to mechanisms of lupus pathogenesis may involve both CD4 + and CD8 + T cells, with IFN-I-stimulated genes expressed in both subsets, Tfh support for pathogenic B cell responses dependent on IFN-I in a STAT4-dependent manner, and IFN-I promoting altered mitochondrial function and lupus-like functional impairment in CD8 + T cells 203 204.…”
Section: Altered Immunoregulationmentioning
confidence: 99%